Pentacyclic triterpenoids from the leaves of Cecropia longipes - Preslav Enchev; Yancho Zarev; Anzhelika Dakovska; Teodora Todorova; Martin Dimitrov; Andrés Rivera-Mondragón; Iliana Ionkova (Pensoft Publishers, 2024)
The genus Cecropia (Urticaceae) comprises 61 tree species primarily found in tropical rainforests from Mexico to South America, including Argentina, Brazil, Paraguay, and Panama. These species are under-researched, with most studies focusing on phenolic derivatives from leaf extracts. Traditionally, Cecropia species are used to treat ailments such as asthma, bronchitis, and diabetes. This study focuses on the underexplored species C. longipes from Panama, aiming to analyze triterpene derivatives in its leaves. Through a series of chromatographic separations and purifications, three pentacyclic triterpenoids were isolated. Using 1D and 2D NMR experiments and HRESI-MS analysis, the following compounds were identified: 19α hydroxyasiatic acid, 1α,3β,23-trihydroxyolean-12-en-28-oic acid, and rosamultic acid. These compounds were isolated for the first time from C. longipes and the genus Cecropia. Genotoxicity tests using S. cerevisiae revealed that two compounds exhibited genotoxic activity at all concentrations. For 19α hydroxyasiatic acid, genotoxic potential was observed at higher concentrations, unrelated to oxidative stress, suggesting other mechanisms.